Simultaneous transabdominal preperitoneal hernia repair and laparoscopic cholecystectomy: A report of 17 cases. Issue 4 (8th November 2018) - Hayakawa, Shunsuke; Hayakawa, Tetsushi; Inukai, Koichi; Miyai, Hirotaka; Yamamoto, Minoru; Kitagami, Hidehiko; Shimizu, Yasunobu; Tanaka, Moritsugu
Abstract: Introduction: Inguinal hernia repair and cholecystectomy are frequently performed in the field of gastrointestinal surgery. However, reports describing surgical procedures that involve simultaneous transabdominal preperitoneal hernia repair (TAPP) and laparoscopic cholecystectomy (LC), as well as the safety and usefulness of this combination, are limited. Herein, we report a surgical procedure involving simultaneous TAPP and LC (TAPP + LC) and present the outcomes of patients who have undergone this combined surgical procedure, with a particular focus on its safety and usefulness. Methods: We simultaneously performed TAPP + LC in 17 patients (mean age, 66.5 ± 8.1 years) with concomitant inguinal hernia and gallbladder stones. We assessed surgical outcomes. Results: The mean operative time was 157 ± 39 min, and mean postoperative hospital stay was 3.2 ± 0.6 days. The median cost was $7673 for TAPP + LC. The mean postoperative length of hospital stay was 1.1 ± 0.6 day for TAPP alone and 3.4 ± 1.4 days for LC alone. The median costs of TAPP alone and LC alone were $4932 and $5453, respectively. Regarding intraoperative complications, the inferior epigastric vessels were damaged in two patients, and seroma was detected as a postoperative complication in one; these complications were spontaneously resolved. No mesh‐ or infection‐related complications were noted. Conclusion: Simultaneous TAPP + LC is safe and can be regarded as a standard surgical procedure for patients with concomitant inguinal hernia and gallbladder stones. The TAPP + LC combination appears to help prevent the need for two hospitalizations and, thereby, reduces hospital stay and economic burden.